2015
DOI: 10.1055/s-0035-1550052
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade Albuminuria Associated with Subclinical Left Ventricular Diastolic Dysfunction and Left Ventricular Remodeling

Abstract: UACR was associated with subclinical LV diastolic dysfunction and remodeling in both patients with and without Type 2 diabetes. We conclude that LGA may also be a marker for subclinical cardiovascular damage in Type 2 diabetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Recently, many researchers have focused on the clinical effects of low-grade albuminuria, which is defined as high level within urinary albumin-to-creatinine ratio (UACR) < 30 mg/g (10)(11)(12)(13)(14)(15)(16). Previous studies have shown an association between a high UACR and various cardiometabolic risk factors (10)(11)(12)(13)(14)(15)(16). In addition, some factors, including various cardiometabolic risk factors, have been shown to predict a high UACR; additional studies investigating new markers of a high UACR are on-going.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers have focused on the clinical effects of low-grade albuminuria, which is defined as high level within urinary albumin-to-creatinine ratio (UACR) < 30 mg/g (10)(11)(12)(13)(14)(15)(16). Previous studies have shown an association between a high UACR and various cardiometabolic risk factors (10)(11)(12)(13)(14)(15)(16). In addition, some factors, including various cardiometabolic risk factors, have been shown to predict a high UACR; additional studies investigating new markers of a high UACR are on-going.…”
Section: Introductionmentioning
confidence: 99%
“…Another study carried out with 760 Chinese participants aged from 29 to 76 years, presenting type 2 DM and normoalbuminuria has demonstrated a signi cant association between LGA and increased thickness of the carotid intima-media layer 20 . UACR was associated with subclinical left ventricular diastolic dysfunction and left ventricular remodeling in patients presenting with and without type 2 DM 19 .…”
Section: Discussionmentioning
confidence: 93%
“…The results of this study demonstrate a signi cant association between LGA and 10-year CVD risk in a sample of hypertensive and/or diabetic patients assisted by PHC. Several other studies associate LGA with increased risk of all-cause cardiovascular disease 12,13,[18][19][20][21] , including in apparently healthy individuals presenting no DM or AH 12 . A study carried out with a nationally representative sample of 9,736 adult Koreans associated albuminuria within the normal range with metabolic syndrome 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease remains the leading cause of death worldwide [1,2]. The prevalence of cardiovascular disease among Chinese population increased steadily, with coronary heart disease (CHD) and stroke accounting for most of deaths [3].…”
Section: Introductionmentioning
confidence: 99%